Worldliness - "Mahaney, C. J."; "Cabaniss, Craig." ("Wheaton, Ill. :")
"Includes bibliographical references (p. 188-191). Is this verse in your Bible? / C.J. Mahaney -- God, my heart, and media / Craig Cabaniss -- God, my heart, and music / Bob Kauflin -- God, my heart, and stuff / Dave Harvey -- God, my heart, and clothes / C.J. Mahaney -- How to love the world / Jeff Purswell."
Keywords: CHRISTIAN LIFE.;WORLDLINESS.